(untitled) (Community Based Medical Journal, 2017)
Heterotopic pregnancy is defined as the co-existence of intrauterine and extrauterine gestation. The ectopic component in this study was in right fallopian tube which ruptured and remained in peritoneal cavity causing acute abdomen and shock. The intrauterine component was a viable existence with 7 weeks of gestation. The ectopic component was managed with immediate laparotomy and resuscitation. The intrauterine component was allowed to continue normally. The course of intrauterine pregnancy was uneventful with successful outcome i.e. a healthy mother delivered a healthy baby at term. We had to adopt Cesarean section due to non- progress of labor. CBMJ 2017 July: Vol. 06 No. 02 P: 21-24